From Social to Educational Entropy. A Reflection on the Colombian Context - Cárdenas Messa, Gustavo Adolfo (2019)
This study sets forth an academic approach that applies the concept of entropy (the second law of thermodynamics) to the foundations of education. The concept of entropy is based on the notion of uncertainty in a changing world that is subject to chance and which is not represented in a static educational system which possesses a degree of theoretical mobility but has little didactic and evaluative mobility. As a result, entropy becomes a favorable setting for the type of transformation that education must undergo to respond to the needs of a non-static system. This article analyzes the context of the Colombian educational system, a low-entropy system that is organized, systematic and hardly adaptable to the changing actuality of our contemporary world.